Facile one-pot four-component synthesis of 3,4-dihydro-2-pyridone derivatives: Novel urease inhibitor scaffold - Arash Modarres Hakimi; Negar Lashgari; Shabnam Mahernia; Ghodsi Mohammadi Ziarani; Massoud Amanlou (Wolters Kluwer Medknow Publications, 2017)
In the current study, a series of 3,4-dihydro-2-pyridone derivatives were synthesized in a one-pot four- component reaction of Meldrum's acid, benzaldehyde derivatives, methyl acetoacetate, and ammonium acetate. SiO2-Pr-SO3H was used as an efficient catalyst for the synthesis of the target compounds under solvent-free conditions. The most probable mechanism for this reaction has been discussed. The advantages of this methodology are high product yields, being environmentally benign, short reaction times, and easy handling. Eight 2-pyridinone derivatives were evaluated for their inhibitory activities against Jack bean urease. Molecular docking study of the synthesized compounds was also evaluated. All compounds showed good activities against urease and among them, 4-(4-nitrophenyl)-5-methoxycarbonyl-6-methyl-3,4- dihydropyridone (5a) showed the most potent activity (IC50 = 29.12 µM), more potent than hydroxyurea as the reference drug (IC50 = 100.0 µM). Also, the results from docking studies were in good agreement with those obtained with in vitro assay. According to the docking studies methionine (Met) 637 and nitro phenyl ring cause n-π interaction between lone pair of sulfur atom and π aromatic ring. Moreover, hydrophobic interactions existed between compound 5a and alanine (ALA) 636, ALA 440, and isoleucine 411. The results indicated that the inhibitory activities increased with the increase of electron withdrawing ability of the groups despite a less important role of lipophilicity in increasing the inhibitory activity.